How Survivors of Abuse Relate to God The Authentic Spirituality of the Annihilated Soul. - Shooter, Susan (Farnham : Ashgate Publishing Ltd, 2012)
Grappling with theological issues raised by abuse, this book argues that the Church should be challenged, and ministered to, by survivors. Paying careful attention to her interviews with Christian women survivors, Shooter finds that through painful experiences of transformation they have surprisingly become potential agents of transformation for others. Shooter brings the survivors' narratives into dialogue with the story of Job and with medieval mystic Marguerite Porete's spirituality of 'annihilation'. Culminating in an engagement with contemporary feminist theology concerning power and powe.
Cover; Contents; List of Tables; Preface; Abbreviations; 1 Introduction: What Lies Beneath; 2 Knocking at the Door: Presenting Issues; 3 Finding the Right Key: A Grounded Qualitative Design; 6 At Home with God: Marguerite Porete's Mirror; 7 The Authentic Spirituality of the Annihilated Soul; 8 What Lies Ahead: Conclusions and Implications; Epilogue; Bibliography; Author Index; Scripture Index; Subject Index
Description based upon print version of record.
Keywords: Abused women -- Religious life; Adult child abuse victims -- Religious life; Child sexual abuse -- Religious aspects -- Christianity; Sexual abuse victims -- Religious life; Religion; Abused women -- Religious life; Adult child abuse victims -- Religious life; Sexual abuse victims -- Religious life; Child sexual abuse -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books